ULTRASTRUCTURE OF THE PLACENTA DURING PARVOVIRUS INFECTION B19 - Bondarenko, N.P.; Stechenko, L.O.; Lakatosh, V.P.; Lakotosh, P.V.; Antonyuk, M.I.; Narytnik, T.T. (World of Medicine and Biology, 2016)
Response in Placental Tissues – cytotrophoblast and plasmodiotrophoblast to parvovirus B19 and its cytotoxic influence on cells cause pathogenic abnormality, such as aborts and fetal death in terms of 21 weeks’ gestation. To cytopathic effect of virus include formation in the nucleus of endothelial cells of blood capillary as well as myelin figures in cytoplasm, which are connected with enchancement of lipid peroxidation. The method of electron microscopy provides additional information about the cause of immature birth and embryofoetal death with non-immune hydrop in the second trimester of pregnancy with ELISA doubtful results on parvovirus infection B19. Parvovirus B19 viral particles imaging in 100% cases of termination with edema syndrome in the fetus and placenta in terms of the 15-19 weeks, at the same time as mothers infected by acute parvovirus infection (detection of human parvovirus B19-specific IgM and IgG antibodies) only in 62,5% cases was diagnosed by ELISA.